Vardenafil oral jellies as a potential approach for management of pediatric irritable bowel syndrome - Eman Gomaa; Margrit M. Ayoub (Elsevier, 2021)
Irritable bowel syndrome (IBS); a widespread disorder in gastrointestinal tract especially in children, burdens their healthcare systems and upsets families. Great attention was paid to understand the pathophysiological cause of disorder. However, developing a convenient treatment especially for children remains a challenge. Phosphodiesterase inhibitors were recently introduced for IBS management. Vardenafil (VDF), a phosphodiesterase-5 inhibitor, exhibiting limited bioavailability when taken orally due to extensive first-pass effect, was the choice for study. This study aimed to formulate VDF jellies as a buccal dosage form to improve pediatric compliance and achieve maximum drug efficacy. VDF oral jellies were prepared by heat and congeal method, and were evaluated for their pH, content uniformity, physical stability, general appearance, and in-vitro drug release. VDF jellies (F1), with satisfactory organoleptic properties and highest percent of drug released compared to other formulations was selected as a master formula for further study to ensure in-vivo efficacy. cyclic Guanosine Mono Phosphate (cGMP), used as indicator of VDF concentration in blood, was highly increased after administration of VDF jellies (F1), compared to oral VDF suspension. Increased defecation with improved fecal consistency strongly favored oral jellies as a potential alternative route for VDF for IBS management with high pediatric acceptance.